The use of the ludic methodology for teaching English to adhd students coursing the cuarto año de educación general básica of the Rumiñahui high school, located in the San Isidro parish from Guano - Chimborazo province, in the academic period 2021-2022 - Pérez Reyes, Leslie Micaela (2022)
Teaching to people with Attention Deficit Hyperactivity Disorder (ADHD) is considered a challenge. Lack of concentration, hyperactivity, impulsivity, episodes of anger, frustration, and problems following orders are the characteristics of this disorder. Therefore, education for people with ADHD has been integrated into inclusive and differentiated education. To overcome it, several innovations in methodologies, techniques, strategies, and tools have been used to improve the teaching and learning process of this population. Among these innovations is the ludic methodology, based on the principle of play and motivation. This methodology supports teaching subjects considered "difficult" such as English. Thus, the objective of this research was the analysis of the usage of ludic methodology to teach English to students with Attention Deficit Hyperactivity Disorder (ADHD), who are in Cuarto Año de Educación General Básica of the Rumiñahui high school, located in the San Isidro parish from Guano-Chimborazo province, in the academic period 2021-2022. For this purpose, the study took a qualitative approach and a descriptive level. The population consisted of three students diagnosed with ADHD and the teacher in charge of the subject of Foreign Languages, who were interviewed and observed in a series of classes. The results suggest that, from the teacher's perspective, applying a ludic methodology to teach English to students with ADHD improves concentration, reduces stress, increases collaborative work, and results in more productive and efficient classes. It shows that no student is a challenge or extra work due to their learning difficulties. It all depends on how the teacher approaches and seeks solutions that encourage him/her to teach any student.